PRESERVING PLANET EARTH - Martin, Jane Roland, 1929- ([S.l.])
1 online resource
Keywords: This book encourages readers to acknowledge humanity's contribution to the environmental crisis, proposing a way forward by exploring the power of ordinary people to bring about large-scale cultural change. Is it possible for humankind to change its ways and shed the belief that the planet is ours to do with as we like? Internationally acclaimed philosopher of education Jane Roland Martin argues that "humancentrism" is a learned affair, and what is learned can be unlearned.Turning to the past to see how large-scale cultural change has occurred, she discovers a pattern in the achievements of such historical luminaries as Martin Luther, Mahatma Gandhi, Rosa Parks and Greta Thunberg that we too can follow.Drawing on history, philosophy, and literature as well as the natural and social sciences and hoping to mobilize readers to effective action, Martin employs an accessible and powerful rhetoric, with each chapter beginning with a scene from history written in dialogue form. This book calls on young and old to avert a looming tragedy of Aristotelian proportions--the demise of the Mother Nature that made it possible for our species to flourish. Thoroughly interdisciplinary in its approach, it will appeal to students and teachers as well as general readers interested in environmental studies, philosophy, and education.